Navigation on the Danube River. International Historical-Legal Aspect: Array - Vdovenko, Tetyana (Journal of Danubian Studies and Research, 2020)
The history of navigation on the Danube river is part of the centuries of history of the countries and peoples who inhabited the banks of the Danube since ancient times. The origins of navigation on the Danube date back to the XVIII century, when after the collapse of the Ottoman Empire, the access to the Black sea was gained. According to the peace Treaty, signed in July, 1774, the right to trade on the Danube both on ships, and on the adjoining land was received. According to the Bucharest peace Treaty with Turkey (1812), the border between the countries began to pass along the Prut river. Changes in the regime of navigation on the Danube in the XVII-XVIII centuries, the development of bourgeois relations and the emergence of large cities on the Danube lands contributed to the revival of foreign trade on the river.